2017
DOI: 10.1038/srep43764
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol depletion impairs contractile machinery in neonatal rat cardiomyocytes

Abstract: Cholesterol regulates numerous cellular processes. Depleting its synthesis in skeletal myofibers induces vacuolization and contraction impairment. However, little is known about how cholesterol reduction affects cardiomyocyte behavior. Here, we deplete cholesterol by incubating neonatal cardiomyocytes with methyl-beta-cyclodextrin. Traction force microscopy shows that lowering cholesterol increases the rate of cell contraction and generates defects in cell relaxation. Cholesterol depletion also increases membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 74 publications
(106 reference statements)
5
40
0
Order By: Relevance
“…Recently, Hissa et al . () have demonstrated that cholesterol depletion in neonatal rat cardiomyocytes impairs contraction and induces myofibril disruption. Likewise, Haque et al .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Hissa et al . () have demonstrated that cholesterol depletion in neonatal rat cardiomyocytes impairs contraction and induces myofibril disruption. Likewise, Haque et al .…”
Section: Discussionmentioning
confidence: 97%
“…Cholesterol sequestration leads to dis-association of proteins from lipid rafts (Scheiffele et al, 1997;Kabouridis et al, 2000;Predescu et al, 2005) and to decrease in clustering of raft-associated molecules (Harder et al, 1998). Cholesterol depletion also disrupts caveolae structure; it does not result in the disappearance of caveolin but leads to a shift of caveolin from raft to non-raft fractions (Hissa et al, 2017) and to ruffling (Grimmer et al, 2002). It was shown that βCDs sequestered cholesterol from both cholesterol-rich and cholesterol-poor membrane domains (Ottico et al, 2003;Gaus et al, 2005;Rouquette-Jazdanian et al, 2006;Tikku et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These combined techniques provide information of the diffusion coefficient of particles in the membrane and also reveal membrane corrals, barriers, and sites of confinement [38]. Finally, other optical techniques have been used to elucidate other features of lipid rafts: fluorescence correlation spectroscopy, to gain information of fluorophore mobility in the membrane [39]; fluorescence resonance energy transfer, to detect when fluorophores are in close proximity [40], and optical tweezers, to give information about the membrane mechanical parameters [8,41]. In the future, it is expected that other super-resolution microscopy techniques, such as stimulated emission depletion microscopy [42] or various forms of structured illumination microscopy may overcome the problems imposed by the diffraction limit.…”
Section: Lipid Raftsmentioning
confidence: 99%
“…Changes in membrane composition, particularly in cholesterol content, have also been shown to influence cell surface tension. MβCD causes an increase in tension in embryonic kidney cells [98], fibroblasts [9] and cardiomyocytes [99]. This increase is not only due to changes in membrane composition, but it also affects the actomyosin cytoskeleton.…”
Section: Actomyosin Cytoskeleton: the Contractile Machinery Of Musclementioning
confidence: 99%
See 1 more Smart Citation